Diabetes and Bone Involvement in Primary Hyperparathyroidism: Literature Review and Our Personal Experience - Castellano, Elena; Attanasio, Roberto; Boriano, Alberto; Borretta, Valentina; Tassone, Francesco; Borretta, Giorgio (Frontiers in Endocrinology, 2021)
Background. Primary hyperparathyroidism (PHPT) and type 2 diabetes mellitus (T2DM) are common endocrine disorders impacting on skeletal health, whose concomitant occurrence is becoming more frequent. Patients and methods. We searched the PubMed database from the National Library of Medicine about the relationship between T2DM and its treatment and bone manifestations of PHPT. Thereafter, we retrospectively evaluated a consecutive series of 472 PHPT patients. Among them 55 were also affected by T2DM. At the diagnosis of PHPT we compared bone turnover markers and bone densitometry between 55 patients with and 417 without T2DM and in the former group according to antidiabetic treatment. Results. Few data are available about T2DM and PHPT bone involvement, studies about T2DM treatments and PHPT bone manifestations are lacking. Among patients with PHPT of our series, those with T2DM were older, had a lower prevalence of osteitis fibrosa cystica, higher lumbar and femoral T-scores than the remaining patients. No difference was disclosed among the diabetic patients according to ongoing antidiabetic treatment, even though modern treatments were under-represented. Conclusions. No clinical study specifically evaluated the impact of T2DM on bone involvement in PHPT. In our experience, diabetic patients resulted more frequently “mild asymptomatic” than non-diabetic patients and showed a lower prevalence of radiological PHPT bone manifestations. The treatment of T2DM do not seem to affect the biochemical or clinical features of PHPT in our series. Further studies are needed to fully disclose the influence of T2DM and antidiabetic treatment on bone health in patients with PHPT.